"Blue-Blood"- Infused Chicken Thigh Training Model for Microsurgery and Supermicrosurgery. Issue 4 (April 2018) - Zeng, Weifeng; Shulzhenko, Nikita O.; Feldman, Conner C.; Dingle, Aaron M.; Poore, Samuel O.
Abstract : Supplemental Digital Content is available in the text.